A Study To Assess The Level Of Depression Among Alcoholics Clients’ Wives In Selected Hospital At Pondicherry - Vendiran, Tamilpula; Danasu, R. (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
Major Depressive Disorder (MDD) is a highly debilitating, chronic, recurrent, and prevalent disorder. While depression symptoms occur along a continuum with subclinical levels occurring in the general population, and there are important correlates associated with subclinical levels of depression, we will focus on the clinical levels of depression associated with MDD. Descriptive research design was used for this study. The qualitative research approach was used for this present study. The study was conducted in SMVMCH at Pondicherry. In this hospital having 750 bedded multi-speciality hospital, Population of study was all alcoholic patient’s wives. Sample size consists of 60 alcoholic clients’ wives at SMVMCH, Convenient sampling technique was used (Begley t., et al (2007).